2019
DOI: 10.3390/atmos10060322
|View full text |Cite
|
Sign up to set email alerts
|

Explosive Cyclogenesis around the Korean Peninsula in May 2016 from a Potential Vorticity Perspective: Case Study and Numerical Simulations

Abstract: An explosive cyclone event that occurred near the Korean Peninsula in early May 2016 is simulated using the Weather Research and Forecasting (WRF) model to examine the developmental mechanisms of the explosive cyclone. After confirming that the WRF model reproduces the synoptic environments and main features of the event well, the favorable environmental conditions for the rapid development of the cyclone are analyzed, and the explosive development mechanisms of the cyclone are investigated with perturbation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…This implies that the ETCs in this region can rapidly intensify through both upper-and lower-level processes. The previous studies indeed confirmed the importance of both dynamic and diabatic processes (Heo et al, 2015;Heo et al, 2019;Lee et al, 1991;Lee et al, 2009). However, most analyses are focused on case studies, and the relative importance of upper-and lower-level processes in the rapid intensification of ETCs is not generalized in this region, although it could vary from one case to another (e.g., Binder et al, 2016).…”
Section: Introductionmentioning
confidence: 70%
“…This implies that the ETCs in this region can rapidly intensify through both upper-and lower-level processes. The previous studies indeed confirmed the importance of both dynamic and diabatic processes (Heo et al, 2015;Heo et al, 2019;Lee et al, 1991;Lee et al, 2009). However, most analyses are focused on case studies, and the relative importance of upper-and lower-level processes in the rapid intensification of ETCs is not generalized in this region, although it could vary from one case to another (e.g., Binder et al, 2016).…”
Section: Introductionmentioning
confidence: 70%
“…In explosive cyclones, the troughs deepen the tropopause over the cold side due to their interaction with air masses. In this case, it is considered that there is a fold in the dynamic tropopause (Uccellini et al, 1985;Avila et al, 2016Avila et al, , 2021Nunes and Avila, 2017;Heo et al, 2019), which entails a maximum of potential vorticity (PV). For the Southern Hemisphere, cyclonic PV is negative, and according to Santurette and Georgiev (2005), 1,5 units of potential vorticity represents dynamic tropopause.…”
Section: Resultsmentioning
confidence: 99%
“…Just like the medicanes, the explosive cyclones also belong to the intense Mediterranean cyclones, though not restricted to the Mediterranean area. They are generally larger in size and have larger lifetimes than the regular medicanes, and their characteristics are similar to tropical cyclones (Heo et al, 2019;Kouroutzoglou et al, 2011Kouroutzoglou et al, , 2014Michaelides et al, 2018). The development mechanisms are related to those of the medicanes described above.…”
Section: Explosive Cyclonesmentioning
confidence: 93%
“…This increased circulation in turn can result into higher diabatic heating by which a feedback develops. It is thought that the feedback mechanism is a main factor in the development of explosive cyclones (Heo et al, 2015;Heo et al, 2019;Kotal et al, 2012;Pang and Fu, 2017).…”
Section: Explosive Cyclonesmentioning
confidence: 99%